Genetic Variation in Caveolin‐1 Correlates With Long‐Term Pancreas Transplant Function. Issue 5 (18th March 2015) - Hamilton, A.; Mittal, S.; Barnardo, M. C. N. M.; Fuggle, S. V.; Friend, P.; Gough, S. C. L.; Simmonds, M. J.
ABSTRACT Pancreas transplantation is a successful treatment for a selected group of people with type 1 diabetes. Continued insulin production can decrease over time and identifying predictors of long‐term graft function is key to improving survival. The aim of this study was to screen subjects for variation in the Caveolin‐1 gene (Cav1), previously shown to correlate with long‐term kidney transplant function. We genotyped 435 pancreas transplant donors and 431 recipients who had undergone pancreas transplantation at the Oxford Transplant Centre, UK, for all known common variation in Cav1. Death‐censored cumulative events were analyzed using Kaplan–Meier and Cox regression. Unlike kidney transplantation, the rs4730751 variant in our pancreas donors or transplant recipients did not correlate with long‐term graft function (p = 0.331–0.905). Presence of rs3801995 TT genotype (p = 0.009) and rs9920 CC/CT genotype (p = 0.010) in our donors did however correlate with reduced long‐term graft survival. Multivariate Cox regression (adjusted for donor and recipient transplant factors) confirmed the association of rs3801995 (p = 0.009, HR = 1.83;[95% CI = 1.16–2.89]) and rs9920 (p = 0.037, HR = 1.63; [95% CI = 1.03–2.73]) with long‐term graft function. This is the first study to provide evidence that donor Cav1 genotype correlates with long‐term pancreas graft function. Screening Cav1 in other datasets is required to confirm these pilot results.